Screening for Cervical Cancer - Patiyus Agustiansyah; Rizal Sanif; Siti Nurmaini; Irfannuddin; Legiran (HM Publisher, 2021)
Screening is a public health intervention administered to a target population without symptoms. Screening is not performed to diagnose a disease, but to identify individuals with a higher likelihood of developing the disease itself or a precursor to the disease. Not all diseases are suitable for screening programs. The following criteria help determine whether a disease is suitable for a screening program: (1) The disease is bound to have serious consequences. (2) The disease must have a detectable preclinical and asymptomatic stage. (3) Treatment at the preclinical stage should influence the long-term course and prognosis of the disease being screened. (4) Care must be available and accessible to those who have a positive screening test. History, screening tests and treatment options for cervical pre-cancer meet these criteria.